(untitled) (REGE Revista de Gestão, 2024)
Purpose – Creating a new product or service promotes the status quo changes, seeking economic value andsolving customer’s urgent problems. Entrepreneurs play an important role in this changing process throughstart-ups and small and medium enterprises (SMEs), considered one of the leading forces driving an economy’sinnovative and competitive power. However, despite the importance of entrepreneurs, public policies to fosterentrepreneurship ecosystems could be ineffective in emerging countries. Therefore, action research proposesthe qualification of entrepreneurs for the structuring of new businesses through remote orientation, connectingthe country’s main economic centers to emerging areas.Design/methodology/approach – The study is qualitative research comprising two phases. The first phaseconsisted of four-month action research, connecting two researchers and three groups of specialists (from SaoPaulo), with three groups of entrepreneurs (located in Manaus in the Amazon region), through a remoteorientation in entrepreneurship, lean start-up, lean product and process development (LPPD). The secondphase, conducted by a third researcher, regards a case study grounded on interviews and data collection withthe entrepreneurs to capture the outcomes of the remote orientation process.Findings – The remote orientation helped shorten the geographical distance of Amazonas to approach theintegration of business, research and knowledge exchange of such distinct areas in the same country. If aremote orientation program was established as public policy, it could enact subsequent cycles of the lean startup model. Furthermore, the remote orientation could be an alternative to compose the training subsystem in theentrepreneurship ecosystem proposed by Isenberg (2011). On the other hand, a remote orientation could fail toshorten the distance of human values and beliefs, which cannot be neglected when facing a rich territory likethe Amazon.Research limitations/implications – Because of the chosen research approach, a qualitative andexploratory study based on a combination of action research, interviews and case studies, the results may lackgeneralizability. However, further studies can replicate the remote orientation process conducted in the regionof Manaus – Amazon, to obtain distinct results regarding the advantages, disadvantages and effectiveness ofremote orientation as entrepreneurship ecosystem’s human capital dimension development.Practical implications – The outcomes of this research have the potential to start discussions regarding theadoption of remote orientation as a public policy to develop entrepreneurship skills in emerging regions, notonly in Brazil but worldwide. The Brazilian case could be a relevant benchmark due to the large territory andeconomic and social disparities impacting education and entrepreneurship.Social implications – Through start-ups and SMEs, entrepreneurship has innovation potential and is themost solid way to bring economic development. For emerging countries, it can be real game-changer in the economic order. The development of entrepreneurship skills through this remote orientation experience canhelp reduce the economic and social gaps in countries with relevant disparities like Brazil and other emergingcountries.Originality/value – This paper fulfills an identified need to “move the needle of entrepreneurship in the rightdirection” (Isenberg, 2010) by creating local solutions for global challenges. Policymakers and leaders need tocontinue the experiment and learn how to improve the entrepreneurship ecosystem. In this sense, the actionresearch approach, combined with the remote orientation, proposes an alternative to promote changes in howhuman capital dimension can be developed in this challenging ecosystem.